Templated solid-state dewetting of single-crystal iron films and specifically localized buckle delamination of surface oxide. (10th October 2018) - Lee, Dongchul; Jeong, Jaehoon; Han, Seungheon; Choi, Kyeonggon; Ye, Jongpil
Abstract: Morphological evolution during the dewetting of single-crystal Fe(100) patches is shown to strongly depend on the patch alignment and annealing ambient owing to the anisotropies of the edge retraction rate and surface energy of iron films. It is also observed that iron films dewet in the presence of continuous iron oxide layers when the hydrogen flow rate is sufficiently low. The oxide layers in the downhill area of thickening rims are shown to be buckle-delaminated, resulting in the formation of oxide membrane patterns on top of the dewetted structures.